Hematology, micronuclei and nuclear abnormalities in fishes from São Francisco river, Minas Gerais state, Brazil - doi: 10.4025/actascibiolsci.v33i1.7117 - Robson Seriani; Maria José Tavares Ranzani-Paiva; Ângela Teresa Silva-Souza; Silvia Roseli Napoleão (Acta Scientiarum. Biological Sciences, 2011)
This study aimed to determine the variables leukocytary, erythrocytary, frequency of micronuclei and nuclear abnormalities in peripheral erythrocytes of Prochilodus argenteus, Pimelodus maculates and Myleus micans from São Francisco river basin, Minas Gerais State, during the summer and winter. Thrombocytes, hematocrit and leukocyte of P.argenteus series, was influenced by climatic conditions. In P. maculatus, not were significant differences for all leukocytes and thrombocytes. In M. micans, values are unprecedented in the literature, with MCV and absolute number of leukocytes found superior to other species of the family Characidae. The frequency of micronuclei and nuclear abnormalities in erythrocytes, the three species not showed seasonal differences between the sites. However, the highest values were found in summer. Furthermore, we observed a positive correlation between the increase in the percentage of micronuclei with nuclear abnormalities.